Correlation between blend morphology and recombination dynamics in additive-added P3HT:PCBM solar cells1. Issue 39 (21st October 2015) - Solanki, Ankur; Wu, Bo; Salim, Teddy; Lam, Yeng Ming; Sum, Tze Chien
<x xml:space="preserve">Abstract</x> The addition of a small amount of high boiling point solvent in organic donor/acceptor blends to control their morphology is one viable approach to enhance the power conversion efficiency of thermal-annealing free bulk heterojunction (BHJ) organic solar cells.